Implementation Of Archive Training Model To Improve The Competence of Teachers and Students of SMK N1 Kisaran - Rotua SP Simanullang; Sri Mutmainnah; Ellys Siregar; Gartima Sitanggang; Aurora Elise Putriku (Outline Publisher, 2025)
The subject of Archives, which is an essential part of the Office Management Expertise Program Curriculum is required for students, focuses on developing archive management skills through various storage methods. This Community Service Activity will be carried out in an effort to improve the professionalism of teachers in the Office Administration Archives training course, designing RKBM, teaching materials, learning media. Community service activities at SMK Negeri 1 Kisaran are focused on developing teacher and student competencies in the field of archives, by utilizing innovative approaches that support learning based on the Independent Curriculum. The outputs produced from this activity include several important aspects. First, training modules and guides for managing electronic and conventional archives are specifically designed to improve teacher skills in managing archives in accordance with the standards of the National Archives of the Republic of Indonesia (ANRI). In addition, learning tools such as the Teaching and Learning Activity Plan (RKBM), teaching modules, and project-based evaluation instruments are also prepared to enrich the archiving learning process in schools.